Bistatic multi‐polarimetric synthetic aperture radar coherence investigation using spatially variant incoherence trimming - Hagelberg, Alexander; Andre, Daniel; Finnis, Mark V. (Institution of Engineering and Technology (IET), 2024)
Synthetic Aperture Radar (SAR) Coherent Change Detection allows for the detection of very small scene changes. This is particularly useful for Intelligence, Surveillance and Reconnaissance as small changes such as vehicle tracks can be identified. Rapidly collecting repeat pass SAR imagery is important in these applications. For space‐borne platforms, such repeat passes may however have significant differences, or baselines. Coherent Change Detection products are reliant on high coherence for good interpretability. This work investigates the sources and levels of incoherence associated with bistatic SAR imagery for a variety of baselines using simulations and measured laboratory data for two ground types. Additionally, spatially variant incoherence trimming is implemented. The paper shows the importance of angle‐dependant backscatter on the coherence of sub‐resolution cell scatterers.
Keywords: Networking & Telecommunications; 4006 Communications engineering; decorrelation; electromagnetic wave scattering; frequency-domain analysis; multistatic radar; polarimetric radar; radar clutter; radar interferometry; remote sensing by radar; synthetic aperture radar; ultra wideband radar